2022
DOI: 10.1002/cam4.5381
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin‐dependent kinase subunit2 (CKS2) promotes malignant phenotypes and epithelial‐mesenchymal transition‐like process in glioma by activating TGFβ/SMAD signaling

Abstract: Background: Gliomas are a group of primary intracranial tumors with high morbidity and mortality. The previous researches indicated a crucial role of CKS2 (cyclin-dependent kinases regulatory subunit 2) in hepatocellular carcinoma and breast cancer; however, little is known about the molecular mechanism of CKS2 in the tumorigenesis and epithelial-mesenchymal transition-like (EMT) process in glioma.Methods: Datasets for bioinformatics analysis were obtained from the GEO, TCGA and CGGA databases. qRT-PCR, wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The article screening process is shown in figure 1. Of the 13 included articles,8 9 19–29 10 were from China, 2 were from Japan and 1 was from South Korea. Their sample size ranged from 38 to 345, with a mean of 103.7.…”
Section: Resultsmentioning
confidence: 99%
“…The article screening process is shown in figure 1. Of the 13 included articles,8 9 19–29 10 were from China, 2 were from Japan and 1 was from South Korea. Their sample size ranged from 38 to 345, with a mean of 103.7.…”
Section: Resultsmentioning
confidence: 99%
“…Our study incorporated data from TCGA and revealed that only CKS2+ iCAFs exhibited significant prognostic relevance ( P <0.05). CKS2 protein binds to the catalytic subunit of cyclin-dependent kinases, thereby activating their biological functions [ 41 , 42 ]. Gene Ontology (GO) annotations associated with CKS2 include cyclin-dependent protein serine/threonine kinase regulator activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ligocki et al identified pathways involved in proliferation such as the WNT [ 56 ], p53, p63 [ 57 ], and c-Myc pathways and were predicted to be important for limbal stem cells and limbal progenitor cells. Furthermore, the novel genes CKS2 , STMN1 , UBE2C , and E2F8 , which encode transcription factors generally known to be involved in cell proliferation [ 58 , 59 , 60 , 61 , 62 ], were reported and were hypothesized to promote proliferation of TACs in the studies by Ligocki et al, Català et al, and Li et al In the studies by Collin et al and Gautam et al, the NF-κB pathway genes REL , RELA , and RELB were shown to be expressed in cell states of the limbal region [ 29 , 30 ]. A recent study showed that RELA is involved in corneal regeneration and maintenance through the retinoic acid pathway, which is implicated in age-related corneal damage [ 63 ].…”
Section: Classical and Novel Marker Genes Defining Cell States In The...mentioning
confidence: 99%